Merleau-Ponty e a filosofia das neurociências o problema da localização de funções cerebrais - Soares, Edvaldo (Editora Oficina Universitária, 2022)
The object of this reflection will focus on the question of localization, generally understood as the theory that conceives that the different mental and motor functions would be 'located' or 'contained' in specific areas of the brain. In other words, mental functions would be associated with specific neural structure activities (DE SOUZA; TEIXEIRA; DE OLIVEIRA et al., 2017; SBICIGO et al., 2016; SOARES, 2003, 2004).